Construction Mechanical Characteristics of Shallow Karst Stratum Cavity and Subway Tunnel under Different Position Relationships - CHEN Jun; HE Xuhu; WANG Xiang; GU Wenjun; CHEN Bing; WANG Shimin (Chengshi guidao jiaotong yanjiu)
［Objective］ The relationship between the cavity and the newly built tunnel is complex, and the cavity in the surrounding rock of the subway tunnel can affect the construction inside the tunnel and the safety of the ground environment. Therefore, it is necessary to explore the influence of different positional relationships between the cavity and the tunnel on mechanical characteristics of the subway tunnel construction. ［Method］ A numerical model is established using ANSYS finite element software to analyze tunnel peripheral displacement, initial support stress, cavity displacement, cavity stress, and land subsidence. ［Result & Conclusion］ The formation of a cavity may change the original stratum stress field, and the stratum stress in a certain range around the cavity will be released. The stress law of the initial support structure after tunnel excavation is basically the same at different cavity locations, and the existence of the cavity does not significantly change the final stress of the initial support structure. In terms of the maximum displacement difference from cavity top to bottom, the largest one occurs in the arch bottom cavity condition, followed by the vault cavity condition, and the smallest occurs in arch waist cavity condition. Under the no cavity, vault cavity, arch waist cavity, and arch bottom cavity conditions, the maximum land subsidence are 5.37 mm, 4.24 mm, 4.84 mm, and 4.42 mm, respectively. Cavities at different locations will not affect the overall trend of land subsidence changes.